Current and Future Pharmacologic Therapies for Diabetic Retinopathy - Villegas, Victor M.; Schwartz, Stephen G. (Current Pharmaceutical Design, 2018)
Background: Currently, diabetic retinopathy is the leading cause of permanent visual loss in workingage adults in industrialized nations. The chronic microangiopathic changes associated with diabetic retinopathy lead to the most common causes of severe permanent visual loss: diabetic macular edema (DME) and proliferative diabetic retinopathy (PDR). Multiple studies have evaluated different pharmacotherapies for different levels of retinopathy. Methods: A review of the pathophysiology of diabetic retinopathy and current and emerging pharmacotherapies for diabetic retinopathy. Results: Historically, DME has been the primary focus of treatment in patients with nonproliferative diabetic retinopathy (NPDR). Due to the rapidly increasing number of agents and treatment options, management algorithms for DME have become increasingly complex. Furthermore, spectral domain optical coherence tomography (OCT) has allowed unparalleled sensitivity and specificity for detecting macular edema. All available intravitreal vascular endothelial growth factor (VEGF) inhibitors have demonstrated efficacy in the treatment of patients with DME and PDR. Intravitreal triamcinolone acetonide has also proven beneficial in diabetic retinopathy. Most recently, various corticosteroids have been designed as sustained-release intraocular implants in order to reduce the burden and risks associated with retreatment. Current research is focused on providing new agents that target alternate pathways and signaling molecules to provide patients with additional therapeutic tools, especially in patients who have an incomplete response to the current medications. Conclusion: Anti-VEGF therapy has revolutionized the medical management of diabetic retinopathy. The most important existing challenges in the treatment of diabetic retinopathy are improving visual outcomes and decreasing the treatment burden associated with repeated intravitreal injections. Combination therapy with anti-VEGF and corticosteroids with other previously available treatments, such as panretinal photocoagulation, may be a reasonable clinical strategy to reduce the intravitreal injections burden. Many exciting novel drugs that target newly discovered pathways hold clinical promise. The results of ongoing randomized clinical trials will answer the important concerns surrounding new drugs and delivery devices: safety and visual outcomes.
Keywords: nonproliferative diabetic retinopathy (NPDR)